Andy Warhol: documentaries and biographical films. Issue 3 (2014) - Elizabeth Joan Kelly
<x xml:space="preserve"> Abstract </x> Purpose – This paper aims to compile an annotated list of films about or pertaining to the artist Andy Warhol. Design/methodology/approach – Films were located using library catalogs, databases and online searches. Selections were evaluated through inspection and both academic and popular film reviews. Inclusion was predicated not only on subject matter and merit but also on availability either on home media or online. Findings – Warhol's many artistic creations can be introduced and evaluated using a combination of visual and auditory representation. Movies and television (TV) depicting Warhol through dramatization, primary source film, biographical documentary and his art in the context of other artists and movements are readily available through a variety of media. Originality/value – The selected titles provide a comprehensive introduction to the scholarly analysis of Warhol's art and work through a format that allows the most extensive representation of Warhol's artistic output.